Morita Equivalence of Nest Algebras - Eleftherakis, G. K. (MATHEMATICA SCANDINAVICA, 2013)
Let N_1 (resp. N_2) be a nest, A (resp. B) be the corresponding nest algebra, A_0 (resp. B_0) be the subalgebra of compact operators. We prove that the nests N_1, N_2 are isomorphic if and only if A and B are weakly-* Morita equivalent if and only if A_0 and B_0 are strongly Morita equivalent. We characterize the nest isomorphisms which implement stable isomorphism between the corresponding nest algebras.